Analysis of Free Convective Jeffery's Fluid with Periodic Permeability and Cattaneo-Christov Heat Transfer⁎. Issue 30 (2018) - Latif, Atifa; Rana, Muhammad Afzal
Abstract: In this study a free convective three-dimensional flow of an incompressible Jeffery's fluid through a highly porous medium bounded by an infinite vertical porous plate subjected to a constant suction is modeled and analyzed theoretically. The permeability of the medium is assumed to be periodic while free stream velocity is assumed to be uniform. The assumption of either constant or time dependent permeability of a porous medium leads to two-dimensional flows, however, the flow becomes three-dimensional due to variable permeability of the porous medium. Cattaneo-Christov approach is used for the transfer of heat in fluid flow. Analytic solutions for velocity field, pressure, skin friction components and temperature distribution are obtained. The effects of physical parameters emerging in the mathematical model of the physical phenomenon on these physical quantities are discussed and visualized graphically. It is noted that main flow velocity component decreases due to enhancement in non-Newtonian parameter, however, pressure rises due to thickening of the fluid.